Applying a new theoretical and methodological approach for behavior-change campaign planning: identifying the critical determinants for reducing littering and evaluating the resulting large-scale campaign - Tobias, Robert; Moraz, Nicole; Degenhardt, Barbara (Frontiers in Psychology, 2024)
Introduction This paper presents a theoretical concept and methodological approach for identifying critical determinants for behavior change interventions. The approach is based on established theories and constructs but represents them in an intervention- instead of questionnaire-oriented form. Six discriminant and targetable dimensions of behavior determinants are proposed: Consideration, feasibility, instrumental evaluation, norms and goals, affective evaluation, and needs and tension states. Methods For estimating the importance of these dimensions for a specific behavior to be changed in a specific situation and population, a quasi-experimental approach is proposed, in which interventions are designed to have effects on one of these dimensions but none on the other dimensions. By measuring changes of the target behavior or its consequences, the impact of each dimension on changing the behavior can be estimated in-situ without questionnaires. The approach was applied to develop a campaign for reducing picnic littering in an urban park in Zurich (Switzerland). In 2019, posters targeting four dimensions were set up during three waves in up to four zones with two control zones without posters. Before, between, and after the intervention waves, for at least 2 weeks, no interventions were in place. The volume of litter was measured on 119 days at 55 points. Results In some cases, the amount of litter was too small for effects to be detected, but where enough littering occurred, posters providing information, inducing positive emotions, or activating reciprocity norms—as well as providing the option of separating fractions of waste for recycling as a structural measure—reduced litter significantly. Interventions targeting the tension state of disgust had no effect. Posters targeting descriptive and injunctive norms increased the amount of litter. Discussion Based on the results of the preparative study, a large-scale campaign was designed, implemented, and evaluated in 2022, which led to promising effects.